Turning negative: micro-steps from negative polarity item to negative-word. (May 2021) - Larrivée, Pierre
Abstract: This paper revisits the debate as to whether n-words such as English nobody, French personne and Italian nessuno are indefinites or intrinsically negative. Intrinsic negative value is diagnozed by use in the three contexts of fragment answers, double negation and constituent negation. Are these criterial contexts involved in a predictable way through the development of future n-words? The question is answered by a detailed study of Polarity Sensitive Items (PSI) that are potentially ambiguous between n-word and negative polarity item (NPI) in four different languages (Finnish, French, American English and Italian). An ordered relation is found from negative fragment answers, that can be evoked by strong NPIs, to double negation and constituent negation, that are communicated by intrinsically negative n-words. Having identified micro-steps into n-word status, the paper demonstrates that n-words are not mere indefinites, and must have an intrinsic negative value. Highlights: N-words really have an intrinsically negative value, unlike Negative Polarity Items (NPIs). Some NPIs can communicate negative fragment answer when they have a majority of uses in strong polarity contexts. Only n-words can enter in constituent negation and double negation uses. There is a pathway of variation and change such that first negative fragment answers and then constituent negation and double negation uses pave the way to becoming negative.